2012
DOI: 10.2131/jts.37.281
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and androgen receptor status in hepatocellular hypertrophy induced by phenobarbital, clofibrate, and piperonyl butoxide in F344 rats

Abstract: -The present study examined hepatic estrogen receptor (ER) and androgen receptor (AR) levels as well as estrogen-signaling status in a model of rat hepatic hypertrophy induced by phenobarbital (PB), chlofibrate (CF), or piperonyl butoxide (PBO). Male F344 rats were fed with PB at 2,500 ppm, CF at 2,500 ppm, and PBO at 20,000 ppm for 3 days, 4 weeks, and 13 weeks. CF and PBO induced diffuse hypertrophy, while centrilobular hypertrophy was observed with PB administration. The levels of mRNA for ERα, AR and leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The female-specifically expressed gene Lifr in ZSF1 liver is an integral component of the glycoprotein-LIFR signaling complex, acts as signal receptor for cytokine leukemia inhibitory factor and other cytokines, and is an estrogen-responsive gene [44]. Our result shows that hepatic Lifr mRNA level was significantly lower in the livers of obese compared to lean females.…”
Section: Discussionmentioning
confidence: 61%
“…The female-specifically expressed gene Lifr in ZSF1 liver is an integral component of the glycoprotein-LIFR signaling complex, acts as signal receptor for cytokine leukemia inhibitory factor and other cytokines, and is an estrogen-responsive gene [44]. Our result shows that hepatic Lifr mRNA level was significantly lower in the livers of obese compared to lean females.…”
Section: Discussionmentioning
confidence: 61%
“…The peroxisomal proliferator response and cytochrome P450 induction associated with PPARa activation probably also explains the greater liver weight associated with increasing dietary MCT since liver hypertrophy is generally associated with this response. 36 Several studies have shown that MCFAs have low-binding affinity for the PPARs; 37,38 therefore, it is likely that PPARa activation by MCT is indirect, and this mechanism will be pursued in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that these compounds regulate the expression of various genes involved in DNA damage and hormone receptors other than metabolic enzymes (32)(33)(34)(35). However, we have yet to identify the genes linking hepatic potency and elevated mutations, and more speciˆcally, we have yet to account for the fact that the most hypertrophic compound (PBO) was not the most eŠective compound (DBDE) in enhancing mutations.…”
Section: Discussionmentioning
confidence: 99%